Pengaruh Faktor Ekonomi dan Sosial terhadap Penyerapan Tenaga Kerja pada Kabupaten/Kota di Provinsi Jambi - Desi Nopiyanti; Zulfanetti Zulfanetti; Helen Parkhurst (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2026)
One key measure of a region's economic growth is the employment rate, as it reflects the ability of the economy to absorb labor and improve community welfare. In Jambi Province, employment opportunities are influenced by several factors, including Gross Regional Domestic Product (GRDP), population growth, and the Human Development Index (HDI). This study aims to analyze the effects of GRDP, population growth, and HDI on employment growth rates across regencies and cities in Jambi Province. The research employs a quantitative approach using panel data regression analysis covering 11 regencies and cities during the period 2017–2023. The findings indicate that GRDP growth, population growth, and HDI simultaneously influence employment levels. Partially, population growth and HDI have significant effects on employment, indicating that improvements in human development and demographic dynamics contribute to labor absorption. Meanwhile, economic growth, as measured by GRDP, has a relatively small negative effect on employment. This suggests that economic expansion does not always generate proportional employment opportunities, possibly due to structural changes and technological developments. Therefore, policies aimed at improving human capital and labor market conditions are essential to support sustainable employment growth in Jambi Province.